(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article reveals the theoretical and practical foundations of developing the professional competence of future physical education teachers. The study analyzes the possibilities of improving the content of professional training based on a learner-centered approach, pedagogical observation, individual and differentiated approaches, motivational activity, methodological competence, and the use of innovative technologies. In addition, the pedagogical significance of developing professional ethics, emotional stability, leadership qualities, and reflective competence in future physical education teachers is substantiated.